Agama dan Alam di Kalimantan Selatan: Analisis Filsafat Ekofeminis: Religion and Nature in South Kalimantan: An Ecofeminist Philosophical Analysis - Kumari, Fatrawati (Information Technology and Science(ITScience), 2025)
This study discusses environmental damage in South Kalimantan, even though the local community adheres to major religions that teach the importance of preserving nature. This irony shows a tendency towards a masculine approach to nature that separates humans, God, and the environment as separate entities, thus perpetuating ecological exploitation and degradation, such as forest fires, floods, and lack of clean water. This study aims to analyse the relationship between religious teachings and environmental damage from the perspective of ecofeminist philosophy. Using a qualitative-descriptive approach and hermeneutic-critical analysis, this study explores religious texts from six religions practised in South Kalimantan as well as the thoughts of ecofeminist figures. The study results show that all religions reject environmental damage and teach a harmonious relationship between humans, nature, and God. The ecofeminist perspective emphasises feminine values, such as care, gentleness, and mutuality in treating nature as an antithesis to masculine domination based on power, exploitation, and hierarchy. This concept aligns with religious and spiritual values that position humans as caliphs and guardians of nature. This study emphasises the importance of reinterpreting religious teachings in a more inclusive, ecological, and egalitarian manner towards nature and strengthening the strategic role of women (and feminine values) in shaping collective ecological awareness. This study contributes to developing contextual environmental ethics based on the spirituality and local wisdom of the people of South Kalimantan.